Graduate competencies as predictors of the pre-service English teachers’ work-readiness - Ann L. Jaca, Cristie; D. Castañeda Jr., Wilson (Institute of Advanced Engineering and Science, 2025)
This study examines the competencies that predict work readiness among the pioneering cohort of English graduates from a newly implemented curriculum. By evaluating graduates’ perceived competencies and work-readiness over the curriculum’s initial four years, the research addresses its relevance with the current demands of the teaching profession. Employing a descriptive-survey quantitative research design and regression analysis, the study evaluated all 43 graduates of bachelor of secondary education (BSEd) major in English. Respondents were assessed on work readiness and core competencies in content, pedagogy, and essential 21st-century skills, including 4Cs (communication, collaboration, critical thinking, and creativity). Findings revealed that, while graduates demonstrate confidence in pedagogy, creativity, and collaboration, there remains a need for a more balanced skill set, particularly in content knowledge and critical thinking. Regression analysis identified that pedagogy, communication, and critical thinking are key predictors of work-readiness, highlighting that these skills significantly enhance graduates’ preparedness for a dynamic workplace. These insights emphasize the need to refine program objectives to support future cohorts better, underscoring the importance of analyzing graduate competencies to improve curriculum design. This study contributes to adapting educational programs and preparing future English teaching professionals to meet the complexities of modern education and evolving workforce demands.